Trypanosoma (Nannomonas) congolense. Molecular characterization of a new genotype from Tsavo, Kenya - Majiwa, Phelix A.O.; Maina, M.; Waitumbi, J.N.; Mihok, S.; Zweygarth, E. (Cambridge University Press, 1993)
Trypanosoma (Nannomonas) congolense comprises morphologically identical but genetically heterogeneous parasites infective to livestock and other mammalian hosts; three different genotypes of this parasite have been described previously. Restriction enzyme fragment length polymorphisms (RFLPs) in both kinetoplast DNA minicircle and nuclear DNA sequences, and randomly amplified polymorphic deoxyribonucleic acid (RAPD) patterns have been used here to demonstrate the existence of another type of T. (N.) congolense that is genotypically distinct from those that have so far been characterized at the molecular level. A highly repetitive, tandemly arranged DNA sequence and oligonucleotide primers, for use in polymerase chain reaction (PCR) amplification are described, which can be used for specific identification of the trypanosome and its distinction from others within the Nannomonas subgenus.